Accumulation of Cytotoxic Skin Resident Memory T Cells and Increased Expression of IL-15 in Lesional Skin of Polymorphic Light Eruption - Patra, VijayKumar; Strobl, Johanna; Atzmüller, Denise; Reininger, Bärbel; Kleissl, Lisa; Gruber-Wackernagel, Alexandra; Nicolas, Jean-Francois; Stary, Georg; Vocanson, Marc; Wolf, Peter (Frontiers in Medicine, 2022)
Patients with polymorphic light eruption (PLE) develop lesions upon the first exposure to sun in spring/summer, but lesions usually subside during season due to the natural (or medical) photohardening. However, these lesions tend to reappear the following year and continue to do so in most patients, suggesting the presence of a disease memory. To study the potential role of skin resident memory T cells (Trm), we investigated the functional phenotype of Trm and the expression of IL-15 in PLE. IL-15 is known to drive Trm proliferation and survival. Multiplex immunofluorescence was used to quantify the expression of CD3, CD4, CD8, CD69, CD103, CD49a, CD11b, CD11c, CD68, granzyme B (GzmB), interferon-gamma (IFN-γ), and IL-15 in formalin-fixed, paraffin-embedded lesional skin samples from PLE patients and healthy skin from control subjects. A massive infiltration of T cells in the dermis and epidermis is observed in PLE, and the majority of these belong to CD8+ T cells (unlike the constitutive T cell population in healthy skin), which express Trm markers (CD69, CD103, CD49a) and produce cytotoxic effector molecules GzmB and IFN-γ. Higher numbers of CD3+ T cells and CD11b+CD68+ macrophages produced IL-15 in the dermis as compared to healthy skin. The dominant accumulation of cytotoxic Trm cells and increased expression of IL-15 in lesional skin of PLE patients strongly indicates the potential role of skin Trm cells in the disease manifestation and recurrence.